ANALISIS IMPLEMENTASI DEEP LEARNING MATA PELAJARAN PJOK PADA KELAS X SMA NEGERI 10 SEMARANG - Ahmad Husnul Mubarok; Ari Dwi Agunanta; Dwi Muhammad Atohillah; Tubagus Herlambang; Sisworo Sisworo (Journal of Physical Activity and Sports (JPAS), 2026)
This study aims to analyze the implementation of the deep learning model in Physical Education, Sport, and Health (PJOK) learning at grade X SMAN 10 Semarang. The research employed a quantitative descriptive design with purposive sampling involving 34 students. The research instrument consisted of a 46-item questionnaire developed based on eight dimensions of deep learning using a 5-point Likert scale. Data were analyzed using descriptive statistics, normality test, homogeneity test, and One-Sample T-Test with SPSS version 25. The results showed that the implementation of deep learning was in the high category with a mean score of 193.03 out of a maximum score of 230. The highest dimension was character and learning independence, while higher-order thinking skills and supportive learning environment were in the moderate category. Hypothesis testing results showed a significance value of 0.000 < 0.05 and a t-value of 15.247 > t-table of 1.692, indicating that deep learning implementation had a significant positive effect on the PJOK learning process. This study concludes that the application of deep learning is able to improve student engagement, independence, collaboration, and meaningful learning experiences, although improvements are still needed in higher-order thinking skills and supportive learning environments.